Ensino de física : análise dos softwares de simulação disponibilizados pelo site Dia a Dia Educação na perspectiva construcionista - Feltrin, Eder Rodolfo (2015)
When dealing with Physics Teaching, this can benefit much from the application of simulation software in the classroom. These software are able to simulate experiments that just happen in large, sophisticated laboratories, or that the school does not have the equipment needed to perform them, as well as modeling natural phenomena and enabling their exploitation through changes of variables. The institutional site Dia a Dia Educação, maintained by the Department of Education of Paraná, offers simulation software in Physics for use in the classroom. However, the teacher needs a pedagogical conceptions focus on producing a restructuring of the learning process so that the technology is in the service of its purposes and never determining them. One of these concepts is constructionism, in which the student interacts with the computer in an active way, "teaching him." In view of these considerations, the following issues are raised: the simulations found at Dia a Dia Educação for Physical Education teaching tools are developed in a constructionist perspective? The simulation software, available on the website Dia a Dia Educação can be used by the teacher in Physics Teaching constructionist way? Therefore, the aim of this study is to analyze, in a constructionist, simulations of Physics, available at the site Dia a Dia Educação. Justifying that such an analysis open reflection for educators to make the use of appropriate software in this discipline, satisfying the process of teaching and learning. The method of analyzing the data collected from the simulations was the Content Analysis. We conclude that to the extent that we analyze the software, it turns out that it is up to the teacher, to work with these technologies, devise a methodology to apply them in their classes, in order to act an active student participation in building his knowledge.